CASH WAQF LINKED SUKUK: ISSUES, CHALLENGES AND FUTURE DIRECTION IN INDONESIA - Yasin, Rozaq Muhammad (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2021)
Cash Waqf Linked Sukuk (CWLS) is the first innovation sukuk-based modern waqf fundraising development issued by the Indonesian government in 2020. People who prefer to channel their social funds in zakat, infaq, and shodaqah make CWLS less desirable. This paper evaluates the issues, challenges and future direction from the issuance of the CWLS series SWR001 by the Indonesian government. This study used systematic literature review analysis and used Publish or Perish software with Google Scholar as the database. A total of 48 articles published from 2016 to 2021 were selected. Object of this research is the SWR001 series. Systematic data analysis is used to define relevant themes within the topic.The dominance of individual waqf (99.6%) shows that even though SWR001 was offered during the Covid-19 pandemic, it is still in demand by investors (wakif). Even so, less than optimal sales results make nadzir having to re-evaluate the implementation of social programs that had been planned before. Issues and challenges in the development of CWLS products include relatively new products, limited distribution partners and nadzir, low coupons, lack of public understanding, contracts, and incomplete literacy causing the potential wakif not to be maximized. In the future, to increase the CWLS collection, stakeholders is need to ensure the information and mobilization through word-of mouth with the objective to create a positive word of CWLS. Improving communication strategies, ease of service and professionalism nadzir to be very important to do.